The Influence of Product Quality and Service on Customer Satisfaction at Pondok Kito & Resto - Yulianti Yustina; Wargo; Saputra, Ahmad Edi (CV. Zabags Qu Publish, 2025)
This study aims to examine the influence of product quality and service quality on customer satisfaction at Pondok Kito & Resto, an MSME operating in Tanjung Jabung Timur Regency. Using a quantitative approach with a causal research design, primary data were collected through questionnaire distributed to 97 respondents, and analyzed using descriptive and inferential statistics, including multiple linear regression. The results show that both product quality and service quality have a significant and positive effect both partially and simultaneously on customer satisfaction. Partial tests (t-tests) of X1 - Y resulted in a significance the calculated t-value of 13.587 far exceeds the table's t-value of 1.661. Thus, Ha is accepted and H0 is rejected. The results of X2 - Y is significance the calculated t-value of 9.035, which is greater than the t table of 1.661. Thus, the alternative hypothesis (Ha) is accepted, and H0 is rejected. The influence of product quality (X1), and service (X2), on customer satisfaction (Y) of Pondok Kito & Resto in Tanjung Jabung Timur Regency. The test results showed that the F value was calculated as 133.758 with a significance value of 0.000. Since the significance value is much smaller than the specified significance level (α = 0.05), it can be concluded that H0 is rejected and Ha is accepted. These findings indicate that high-performing and reliable products, as well as responsive and empathetic services, contribute directly to a better customer experience. The contribution of this research lies in offering empirical insights that reinforce the integration of quality management strategies in MSMEs to enhance customer loyalty and long-term competitiveness in the culinary sector.